A Pilot Study with Randomised Controlled Design Comparing TiZr Alloy Dental Implants to Ti Implants - Kristina Hultin; Annelie Eriksson; Christina Backe; Ulf Johansson; Kostas Bougas (Stilus Optimus, 2020)
Objectives: Evidence on the clinical performance of recently introduced dental implants in titanium-zirconium alloy is sparse. The aim of the present pilot study with randomized controlled design is to compare changes in supporting structures around dental titanium-zirconium alloy implants to commercially pure titanium implants. Material and Methods: The present material includes consecutive patients referred to a specialist clinic in Sweden. Two patient groups treated with dental implants in two different materials - titanium (Ti) and titanium-zirconium (TiZr) - were defined after block randomisation for smoking. In total, 40 implants installed in 21 patients were available for one-year follow-up. Marginal bone level, soft tissue height and width of keratinised mucosa were registered at baseline and at one-year follow-up. Results: At implant level, the test group (TiZr) yielded significant marginal bone loss (P < 0.001) after one year. Additionally, marginal bone loss after one year was significantly higher for TiZr implants (P < 0.001) as compared to traditional Ti implants. Soft tissue dimensions were stable throughout the evaluation time for both implant materials. Conclusions: One-year results indicate more pronounced initial marginal bone loss for dental implants in titanium-zirconium alloy as compared to implants made of commercially pure titanium.